Cubane Electrochemistry: Direct Conversion of Cubane Carboxylic Acids to Alkoxy Cubanes Using the Hofer–Moest Reaction under Flow Conditions. Issue 2 (7th November 2019) - Collin, Diego E.; Folgueiras‐Amador, Ana A.; Pletcher, Derek; Light, Mark E.; Linclau, Bruno; Brown, Richard C. D.
Abstract: The highly strained cubane system is of great interest as a scaffold and rigid linker in both pharmaceutical and materials chemistry. The first electrochemical functionalisation of cubane by oxidative decarboxylative ether formation (Hofer–Moest reaction) was demonstrated. The mild conditions are compatible with the presence of other oxidisable functional groups, and the use of flow electrochemical conditions allows straightforward upscaling. Abstract : Just go with the flow : Oxidative anodic decarboxylation of cubane carboxylic acids leading to cubyl ethers is described. This first direct electrochemical functionalisation at the cubane system is chemoselective and scalable, with yields of up to 60 % (see scheme).